Excessive Use of Azithromycin in Pakistan amidst the Covid Pandemic - Shaikh, Hafsa (Journal of the Pakistan Medical Association, 2021)
The COVID pandemic has so far taken the lives of millions of people and is now experiencing a second wave. Excessive use of Azithromycin has become very common in Pakistan during this Pandemic . This can lead to development of drug resistance in a population which already has very limited antibiotic options available. Therefore it is necessary to follow antibiotic stewardship guidelines and impose laws that prevent sales of non-prescription antibiotic . Continuous...